ChemInform Abstract: Second Generation Nitrogen Doped Titania Nanoparticles: A Comprehensive Electronic and Microstructural Picture. Issue 9 (March 2015) - Spadavecchia, Francesca; Ceotto, Michele; Presti, Leonardo Lo; Aieta, Chiara; Biraghi, Iolanda; Meroni, Daniela; Ardizzone, Silvia; Cappelletti, Giuseppe
Abstract Review: 213 refs.